The effect of absorption ratio on meltpool features in laser-based powder bed fusion of IN718. (September 2022) - Khorasani, Mahyar; Ghasemi, AmirHossein; Leary, Martin; Sharabian, Elmira; Cordova, Laura; Gibson, Ian; Downing, David; Bateman, Stuart; Brandt, Milan; Rolfe, Bernard
Highlight: The effect of different process parameters on laser absorption ratio, meltpool temperature, and meltpool depth have been investigated. The mechanism of irradiation and reflection in meltpool have been studied. The mathematical model between absorption ratio as a function of scanning speed and laser power is developed. Abstract: The purpose of this research is to develop a hybrid experimental and computational model to estimate the absorption of the laser for Laser-Based Powder Bed Fusion (LB-PBF) of IN718. The research also aims to find an underlying knowledge on the effect of absorption ratio on meltpool morphology. This model helps to improve the accuracy of the prediction of the meltpool morphology and the rheology of the melt tracks as well as the temperature-related phenomena in the process. In this paper, two test sets for the initial test with constant and dynamic/(process parameters dependent) absorption ratios were simulated. Melt tracks with different process parameters are printed and simulated from low to high energy density. Then, the Absorption Ratio (AR) is changed for each simulation until the same meltpool depth as the experimental results is obtained. In the next step, the temperature of the meltpool in the interaction area of the laser and material is measured from the performed simulations. Based on the obtained temperature and process parameters, a mathematical model is developed to estimate the absorption ratio in different conditions. The model is validated in hybrid computational and experimental conditions. The investigation provides the first model to calculate the absorption ratio in LB-PBF based on the temperature of the meltpool and process parameters. Results show that the developed model significantly enhances the accuracy of estimating meltpool features such as temperature, rheological and thermophysical properties of the material in the melting state.